BUMN (State-Owned Enterprises) As a Corporation: A Reflection from Indonesia - Teuku Syahrul Ansari; Herdi Sahrasad; Muhammad Ridwan; Imam Budi Santoso (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This paper describes the role of BUMN (State-Owned Enterprises) as a corporation based on experience in Indonesia. In this context, this paper explains that various studies on the factors of legal certainty and legal relations and growth show that law enforcement is especially important for companies, including BUMN (State-Owned Enterprises). In this case, an independent court is the central institution for upholding the law. Likewise, laws and regulations, for example in the field of capital market law, which prohibit insider trading, for example, lead to the development of the capital market. Likewise, the study of the role of banking law where regulations that encourage and facilitate private monitoring of banks tend to strengthen the appearance of banks, reduce bad loans and strengthen bank stability. In sum, BUMN as one of the actors of economic activity in the national economy has an important role in realizing the welfare of the community. For this reason, the BUMN Law wants to optimize the implementation of the role of BUMN in the national economy in order to realize public welfare. Optimizing the role of SOEs is carried out professionally.